2014
DOI: 10.1089/end.2013.0098
|View full text |Cite
|
Sign up to set email alerts
|

Result of Endoureterotomy in the Management of Primary Obstructive Megaureter in the First Year of Life: Preliminary Report

Abstract: According to the results of our study, endoureterotomy may be an alternative in management of POMU. Of course, further studies with longer follow-up periods are needed to confirm the applicability of this method in patients younger than 1 year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…31 Endoureterotomy has a high success rate, even for patients under 1 year of age, avoiding complications associated with open surgery. 32 A ureter with a diameter of more than 15-25 mm is one of the contraindications for endoscopic balloon dilation. In these cases, the authors found, according to existing information in the literature, that ureterovesical reimplantation with ureteral remodeling provides superior results on peristaltic improvement and postoperative evolution.…”
Section: Discussionmentioning
confidence: 99%
“…31 Endoureterotomy has a high success rate, even for patients under 1 year of age, avoiding complications associated with open surgery. 32 A ureter with a diameter of more than 15-25 mm is one of the contraindications for endoscopic balloon dilation. In these cases, the authors found, according to existing information in the literature, that ureterovesical reimplantation with ureteral remodeling provides superior results on peristaltic improvement and postoperative evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Follow-up of 1 to 4 years achieved free drainage with a marked reduction in proximal stasis and freedom from recurrent infection and pain (51). Endoureterotomy using pure cutting current was also applied in the pediatric population, achieving satisfactory success rates of approximately 90% with a low incidence of complications (52,53). Electrocauter y incisions of fer precise control of t he incision widt h and lengt h and immediate local hemostasis (52).…”
Section: Endoureterotomymentioning
confidence: 99%
“…De s pit e t he c ut t i ng mo d a l it y, endoureterotomy appears to be safer, easier, and less invasive than open surgical management. It prevents damage to the vasculature near the distal ureter and decreases the rate of postoperative morbidity and costs compared with ureteral reimplantation, although its applicability needs to be validated (53).…”
Section: Endoureterotomymentioning
confidence: 99%